Perception of nursing in Primary Health Care about patients with hypertension: does King explain? - Sara Taciana Firmino Bezerra; Maria Vilaní Cavalcante Guedes; Lúcia de Fátima da Silva
ABSTRACT Objectives: to understand nurses' perceptions about Imogene King's concepts on CMIOS and its association with caring for patients with hypertension in Primary Health Care. Methods: a qualitative interventionist research with Family Health Strategy nurses who care for patients with hypertension at Primary Health Care in Maracanaú-CE. A focus group was held with seven nurses, in two audio-recorded and transcribed meetings, to analyze the production of meanings based on discursive practices. Results: the categories personal system, interpersonal system, and social system emerged referring to the potentialities and difficulties found both for understanding concepts, but also in the interaction with oneself, with hypertensive patients and health organization, with a view to adequate care for hypertensive patients. Final Considerations: it was verified the understanding of nurses' knowledge in relation to King's concepts, associating its application in the context of care for patients with hypertension.